Trypanosoma cruzi transmission in a Colombian Caribbean region suggests that secondary vectors play an important epidemiological role (2014)
ABSTRACT: Background: Colombia, as part of The Andean Countries Initiative has given priority to triatomine control programs to eliminate primary (domiciliated) vector species such as Rhodnius prolixus and Triatoma dimidiata. However, recent events of Trypanosoma cruzi transmission in localities where R. prolixus and T. dimidiata are not present suggest that other species are involved in the T. cruzi transmission cycle. Methods: We studied T. cruzi transmission on Margarita Island, located on the Magdalena River in the Colombian Caribbean region, where a high number of non-domiciliated triatomines infected with T. cruzi inside human dwellings have been observed. A cross-sectional survey including serological studies in humans and parasitological and molecular methods in vectors and reservoirs was conducted. We investigated risk factors for human infection and house infestation, and evaluated the association between abundance of wild triatomines in palm trees (Attalea butyracea) across municipalities, seasons and anthropogenic land use. Results: The T. cruzi seroprevalence rate in humans was 1.7% (13/743) and autochthonous active T. cruzi transmission was detected. The infection risk was associated with the capture of triatomines in human dwellings. Five wild mammal species were infected with T. cruzi, where Didelphis marsupialis was the main reservoir host with an 86.3% (19/22) infection rate. TcIb was the only genotype present among vectors. Triatomine abundance was significantly higher in Ecosystem 2, as well as in the dry season. Despite the absence of triatomine domiciliation in this area, T. cruzi active transmission was registered with a human seroprevalence rate similar to that reported in areas with domesticated R. prolixus. Conclusions: This study illustrates the importance of secondary and household invading triatomines in Chagas disease epidemiology in the Caribbean lowlands of Colombia.